Senior female celebrity's body and ageing well discourse on Instagram - Stephani, Nicky (Jurnal Studi Komunikasi, 2022)
Society expects women always to maintain their physical appearance throughout the ages. We can see this condition from the public's view of senior female celebrities, an example of successful ageing or ageing well. This study explores the visual discourse of femininity over the age of 50, which emerges from the Instagram accounts of senior female celebrities. Multimodal critical discourse analysis was conducted on images and texts to reveal dominant themes and rhetorical elements inherent in the femininity of senior female celebrities. The concepts of representation, body and femininity, ageism, and social media analyse alternative discourse related to ageing femininity. This study denotes that the ageing discourse of senior female celebrities reflects the dialectic of realising or revising sexist and ageist ideas about how women look after they reach old age.